GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Indigo-dyed cellulose fibers and synthetic polymers in surface-feeding seabird chick regurgitates from the Gulf of Alaska - Paolo Tremolada; Francesco Saliu; Anna Winkler; Cecilia P. Carniti; Melisa Castelli; Marina Lasagni; Sergio Andò; Don-Jean Leandri-Breton; Marie Claire Gatt; Joan Ferrer Obiol; Marco Parolini; Chinatsu Nakajima; et al. (Marine Pollution Bulletin, 2024)

Residual impacts of a wildland urban interface fire on urban particulate matter and dust: a study from the Marshall Fire - Jonathan M. Silberstein; Liora E. Mael; Caroline R. Frischmon; Emma S. Rieves; Evan R. Coffey; Trupti Das; William Dresser; Avery C. Hatch; Jyotishree Nath; Helena O. Pliszka; Colleen E. Reid; Marina E. Vance; et al. (Air Quality, Atmosphere & Health, 2023)
The impacts of wildfires along the wildland urban interface (WUI) on atmospheric particulate concentrations and composition are an understudied source of air pollution exposure. To assess the residual impacts of the 2021 Marshall Fire (Colorado), a wildfire that predominantly burned homes and other human-made materials, on homes within the fire perimeter that escaped the fire, we performed a combination of fine particulate matter (PM 2.5 ) filter sampling and chemical analysis, indoor dust collection and chemical analysis, community scale PurpleAir PM 2.5 analysis, and indoor particle number concentration measurements. Following the fire, the chemical speciation of dust collected in smoke-affected homes in the burned zone showed elevated concentrations of the biomass burning marker levoglucosan (median levo = 4147 ng g −1 ), EPA priority toxic polycyclic aromatic hydrocarbons (median Σ 16 PAH = 1859.3 ng g −1 ), and metals (median Σ 20 Metals = 34.6 mg g −1 ) when compared to samples collected in homes outside of the burn zone 6 months after the fire. As indoor dust particles are often resuspended and can become airborne, the enhanced concentration of hazardous metals and organics within dust samples may pose a threat to human health. Indoor airborne particulate organic carbon (median = 1.91 μg m −3 ), particulate elemental carbon (median = .02 μg m −3 ), and quantified semi-volatile organic species in PM 2.5 were found in concentrations comparable to ambient air in urban areas across the USA. Particle number and size distribution analysis at a heavily instrumented supersite home located immediately next to the burned area showed indoor particulates in low concentrations (below 10 μg m −3 ) across various sizes of PM (12 nm–20 μm), but were elevated by resuspension from human activity, including cleaning. Graphical Abstract

In utero exposure to diethylstilbestrol and blood DNA methylation in adult women: Results from a meta-analysis of two cohort studies - Clara Bodelon; Gretchen L. Gierach; Elizabeth E. Hatch; Emily Riseberg; Amy Hutchinson; Meredith Yeager; Dale P. Sandler; Jack A. Taylor; Robert N. Hoover; Zongli Xu; Linda Titus; Julie R. Palmer; et al. (Environmental Research, 2023)

Age-Related Interactions with Wind During Migration Support the Hypothesis of Developmental Learning in a Migrating Long-Lived Seabird - Kevin D. Powers; Isabeau Pratte; Robert A. Ronconi; Sarah N. P. Wong; Peter G. Ryan; Linda J. Welch; Tammy L. Silva; Kent A. Hatch; Andrew J. Westgate; David N. Wiley (Frontiers in Marine Science, 2022)
Wind patterns shape migratory pathways and detours of many procellariiform bird species that seasonally migrate between hemispheres. These seabirds are long-lived, and the period of immaturity is presumed to be a time of development and learning the environment, specifically how to use wind to their advantage. We assess how wind encountered by individual Great Shearwaters ( Ardenna gravis ) varies along the migration journey and compare responses between presumed mature and immature birds (early and late, respectively) in southbound migration and mature birds in northbound migration. We analyze modeled Argos locations from 71 individual tracks of migratory Great Shearwaters with concurrent U (East/West) and V (North/South) wind components. Migration in seabirds is well studied, but there is limited quantitative work measuring individual birds directly interacting with wind and their associated changes in flight behavior during migration. We show that Great Shearwaters made optimal use of winds, and that different age groups made decisions that exposed them to different wind constraints. Overall, Great Shearwaters derived positive responses from wind under most conditions and did not rely on a drifting strategy, which would be suggested if wind effect (difference between ground and airspeed) was predominantly positive during migrations. Instead, they appeared to use a compensating strategy to achieve an acceptable course and speed. The difference we observed in migration phenologies suggests that by migrating later, immature birds might travel the path of least resistance and experience flight conditions that are less risky furthering their ability to withstand a variety of wind conditions encountered later in life as done by adults, which migrate earlier and are subject to more variable flight conditions. We conclude that like other procellariiforms, a longer period of sexual maturity is required to enhance flight performance and mediate energy expenditure through experiential learning and increased fitness.

Is Greenness Associated with Dementia? A Systematic Review and Dose–Response Meta-analysis - Federico Zagnoli; Tommaso Filippini; Marcia P. Jimenez; Lauren A. Wise; Elizabeth E. Hatch; Marco Vinceti (Current Environmental Health Reports, 2022)
Purpose of Review We assessed the relation between environmental greenness and risk of dementia and cognitive impairment, based on a systematic review and meta-analysis up to March 30, 2022, characterizing whenever possible the shape of the association using dose–response meta-analysis. Recent Findings Twelve studies were included in this review, either using normalized difference vegetation index (NDVI) or land use/cover (LU/LC) methodology to assess greenness. Comparing the highest versus lowest exposure categories of greenness assessed using the NDVI (6 studies) or LU/LC (6 studies), we found no association with dementia. Dose–response meta-analysis of the association between greenness measured by LU/LC and dementia, based on only 3 studies, indicated a U-shaped association, but estimates were imprecise. Summary Our systematic review and meta-analysis provided some evidence of a slight inverse association between greenness and dementia at intermediate exposure levels, but not at high levels. Potential methodological limitations, such as exposure misclassification and unmeasured confounding, may have affected the results.

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

Corrigendum: Large Vessel Activity and Low-Frequency Underwater Sound Benchmarks in United States Waters - Samara M. Haver; Jeffrey D. Adams; Leila T. Hatch; Sofie M. Van Parijs; Robert P. Dziak; Joseph Haxel; Scott A. Heppell; Megan F. McKenna; David K. Mellinger; Jason Gedamke (Frontiers in Marine Science, 2022)

Large Vessel Activity and Low-Frequency Underwater Sound Benchmarks in United States Waters - Samara M. Haver; Jeffrey D. Adams; Leila T. Hatch; Sofie M. Van Parijs; Robert P. Dziak; Joseph Haxel; Scott A. Heppell; Megan F. McKenna; David K. Mellinger; Jason Gedamke (Frontiers in Marine Science, 2021)
Chronic low-frequency noise from commercial shipping is a worldwide threat to marine animals that rely on sound for essential life functions. Although the U.S. National Oceanic and Atmospheric Administration recognizes the potential negative impacts of shipping noise in marine environments, there are currently no standard metrics to monitor and quantify shipping noise in U.S. marine waters. However, one-third octave band acoustic measurements centered at 63 and 125 Hz are used as international (European Union Marine Strategy Framework Directive) indicators for underwater ambient noise levels driven by shipping activity. We apply these metrics to passive acoustic monitoring data collected over 20 months in 2016–2017 at five dispersed sites throughout the U.S. Exclusive Economic Zone: Alaskan Arctic, Hawaii, Gulf of Mexico, Northeast Canyons and Seamounts Marine National Monument (Northwest Atlantic), and Cordell Bank National Marine Sanctuary (Northeast Pacific). To verify the relationship between shipping activity and underwater sound levels, vessel movement data from the Automatic Identification System (AIS) were paired to each passive acoustic monitoring site. Daily average sound levels were consistently near to or higher than 100 dB re 1 μPa in both the 63 and 125 Hz one-third octave bands at sites with high levels of shipping traffic (Gulf of Mexico, Northeast Canyons and Seamounts, and Cordell Bank). Where cargo vessels were less common (the Arctic and Hawaii), daily average sound levels were comparatively lower. Specifically, sound levels were ∼20 dB lower year-round in Hawaii and ∼10-20 dB lower in the Alaskan Arctic, depending on the season. Although these band-level measurements can only generally facilitate differentiation of sound sources, these results demonstrate that international acoustic indicators of commercial shipping can be applied to data collected in U.S. waters as a unified metric to approximate the influence of shipping as a driver of ambient noise levels, provide critical information to managers and policy makers about the status of marine environments, and to identify places and times for more detailed investigation regarding environmental impacts.

The Next Wave of Passive Acoustic Data Management: How Centralized Access Can Enhance Science - Carrie C. Wall; Samara M. Haver; Leila T. Hatch; Jennifer Miksis-Olds; Rob Bochenek; Robert P. Dziak; Jason Gedamke (Frontiers in Marine Science, 2021)
Passive acoustic data collection has grown exponentially over the past decade resulting in petabytes of data that document our ocean soundscapes. This effort has resulted in two big data challenges: (1) the curation, management, and global dissemination of passive acoustic datasets and (2) efficiently extracting critical information and comparing it to other datasets in the context of ecosystem-based research and management. To address the former, the NOAA National Centers for Environmental Information recently established an archive for passive acoustic data. This fast-growing archive currently contains over 100 TB of passive acoustic audio files mainly collected from stationary recorders throughout waters in the United States. These datasets are documented with standards-based metadata and are freely available to the public. To begin to address the latter, through standardized processing and centralized stewardship and access, we provide a previously unattainable comparison of first order sound level-patterns from archived data collected across three distinctly separate long-term passive acoustic monitoring (PAM) efforts conducted at regional and national scales: NOAA/National Park Service Ocean Noise Reference Station Network, the Atlantic Deepwater Ecosystem Observatory Network, and the Sanctuary Soundscape Monitoring Project. Nine sites were selected from these projects covering the Alaskan Arctic, Northeast and Central Pacific, Gulf of Mexico, Caribbean Sea, and Mid and Northwest Atlantic. Sites could generally be categorized into those strongly influenced by anthropogenic noise (e.g., vessel traffic) and those that were not. Higher sound levels, specifically for lower frequencies (<125 Hz), and proximity to densely populated coastal zones were common characteristics of sites influenced by anthropogenic noise. Conversely, sites with lower overall sound levels and away from dense populations resulted in soundscape patterns influenced by biological sources. Seasonal variability in sound levels across selected decidecade bands was apparent for most sites and often represented changes in the presence or behavior of sound-producing species. This first order examination of levels across projects highlights the utility of these initial metrics to identify patterns that can then be examined in more detail. Finally, to help the PAM community collectively and collaboratively move forward, we propose the next frontier for scalable data stewardship, access, and processing flow.

Reduction of Low-Frequency Vessel Noise in Monterey Bay National Marine Sanctuary During the COVID-19 Pandemic - John P. Ryan; John E. Joseph; Tetyana Margolina; Leila T. Hatch; Alyson Azzara; Alexis Reyes; Brandon L. Southall; Andrew DeVogelaere; Lindsey E. Peavey Reeves; Yanwu Zhang; Danelle E. Cline; Brent Jones; et al. (Frontiers in Marine Science, 2021)
Low-frequency sound from large vessels is a major, global source of ocean noise that can interfere with acoustic communication for a variety of marine animals. Changes in vessel activity provide opportunities to quantify relationships between vessel traffic levels and soundscape conditions in biologically important habitats. Using continuous deep-sea (890 m) recordings acquired ∼20 km (closest point of approach) from offshore shipping lanes, we observed reduction of low-frequency noise within Monterey Bay National Marine Sanctuary (California, United States) associated with changes in vessel traffic during the onset of the COVID-19 pandemic. Acoustic modeling shows that the recording site receives low-frequency vessel noise primarily from the regional shipping lanes rather than via the Sound Fixing and Ranging (SOFAR) channel. Monthly geometric means and percentiles of spectrum levels in the one-third octave band centered at 63 Hz during 2020 were compared with those from the same months of 2018–2019. Spectrum levels were persistently and significantly lower during February through July 2020, although a partial rebound in ambient noise levels was indicated by July. Mean spectrum levels during 2020 were more than 1 dB re 1 μPa 2 Hz –1 below those of a previous year during 4 months. The lowest spectrum levels, in June 2020, were as much as 1.9 (mean) and 2.4 (25% exceedance level) dB re 1 μPa 2 Hz –1 below levels of previous years. Spectrum levels during 2020 were significantly correlated with large-vessel total gross tonnage derived from economic data, summed across all California ports ( r = 0.81, p < 0.05; adjusted r 2 = 0.58). They were more highly correlated with regional presence of large vessels, quantified from Automatic Identification System (AIS) vessel tracking data weighted according to vessel speed and modeled acoustic transmission loss ( r = 0.92, p < 0.01; adjusted r 2 = 0.81). Within the 3-year study period, February–June 2020 exhibited persistently quiet low-frequency noise and anomalously low statewide port activity and regional large-vessel presence. The results illustrate the ephemeral nature of noise pollution by documenting how it responds rapidly to changes in offshore large-vessel traffic, and how this anthropogenic imprint reaches habitat remote from major ports and shipping lanes.

Exploring movement patterns and changing distributions of baleen whales in the western North Atlantic using a decade of passive acoustic data - Genevieve E. Davis; Mark F. Baumgartner; Peter J. Corkeron; Joel Bell; Catherine Berchok; Julianne M. Bonnell; Jacqueline Bort Thornton; Solange Brault; Gary A. Buchanan; Danielle M. Cholewiak; Christopher W. Clark; Julien Delarue; et al. (Global Change Biology, 2020)
Six baleen whale species are found in the temperate western North Atlantic Ocean, with limited information existing on the distribution and movement patterns for most. There is mounting evidence of distributional shifts in many species, including marine mammals, likely because of climate‐driven changes in ocean temperature and circulation. Previous acoustic studies examined the occurrence of minke ( Balaenoptera acutorostrata ) and North Atlantic right whales (NARW; Eubalaena glacialis ). This study assesses the acoustic presence of humpback ( Megaptera novaeangliae ), sei ( B. borealis ), fin ( B. physalus ), and blue whales ( B. musculus ) over a decade, based on daily detections of their vocalizations. Data collected from 2004 to 2014 on 281 bottom‐mounted recorders, totaling 35,033 days, were processed using automated detection software and screened for each species' presence. A published study on NARW acoustics revealed significant changes in occurrence patterns between the periods of 2004–2010 and 2011–2014; therefore, these same time periods were examined here. All four species were present from the Southeast United States to Greenland; humpback whales were also present in the Caribbean. All species occurred throughout all regions in the winter, suggesting that baleen whales are widely distributed during these months. Each of the species showed significant changes in acoustic occurrence after 2010. Similar to NARWs, sei whales had higher acoustic occurrence in mid‐Atlantic regions after 2010. Fin, blue, and sei whales were more frequently detected in the northern latitudes of the study area after 2010. Despite this general northward shift, all four species were detected less on the Scotian Shelf area after 2010, matching documented shifts in prey availability in this region. A decade of acoustic observations have shown important distributional changes over the range of baleen whales, mirroring known climatic shifts and identifying new habitats that will require further protection from anthropogenic threats like fixed fishing gear, shipping, and noise pollution.

Comparing the Underwater Soundscapes of Four U.S. National Parks and Marine Sanctuaries - Samara M. Haver; Michelle E. H. Fournet; Robert P. Dziak; Christine Gabriele; Jason Gedamke; Leila T. Hatch; Joseph Haxel; Scott A. Heppell; Megan F. McKenna; David K. Mellinger; Sofie M. Van Parijs (Frontiers in Marine Science, 2019)

Effects of developmental conditions on growth, stress and telomeres in black‐legged kittiwake chicks - Rebecca C. Young; Jorg Welcker; Christopher P. Barger; Scott A. Hatch; Thomas Merkling; Evgenia V. Kitaiskaia; Mark F. Haussmann; Alexander S. Kitaysky (Molecular Ecology, 2017)
Early‐life conditions can drive ageing patterns and life history strategies throughout the lifespan. Certain social, genetic and nutritional developmental conditions are more likely to produce high‐quality offspring: those with good likelihood of recruitment and productivity. Here, we call such conditions “favoured states” and explore their relationship with physiological variables during development in a long‐lived seabird, the black‐legged kittiwake ( Rissa tridactyla ). Two favoured states were experimentally generated by manipulation of food availability and brood size, while hatching order and sex were also explored as naturally generating favoured states. Thus, the favoured states we explored were high food availability, lower levels of sibling competition, hatching first and male sex. We tested the effects of favoured developmental conditions on growth, stress, telomere length (a molecular marker associated with lifespan) and nestling survival. Generation of favoured states through manipulation of both the nutritional and social environments furthered our understanding of their relative contributions to development and phenotype: increased food availability led to larger body size, reduced stress and higher antioxidant status, while lower sibling competition (social environment) led to lower telomere loss and longer telomere lengths in fledglings. Telomere length predicted nestling survival, and wing growth was also positively correlated with telomere length, supporting the idea that telomeres may indicate individual quality, mediated by favoured states.

Genetic sources of individual variation in parental care behavior - Daniel P. Wetzel; Margret I. Hatch; David F. Westneat (Behavioral Ecology and Sociobiology, 2015)

Rapid ecosystem response to restoration in an urban stream - Clay P. Arango; Paul W. James; Kyle B. Hatch (Hydrobiologia, 2015)

Effect of the nitrification inhibitor dicyandiamide on microbial communities and N2O from an arable soil fertilized with ammonium sulphate - J. Carneiro; L. M. Cardenas; D. J. Hatch; H. Trindade; D. Scholefield; C. D. Clegg; P. Hobbs (Environmental Chemistry Letters, 2010)

Iteroparity in complex mating systems of steelhead Oncorhynchus mykiss (Walbaum) - S. R. Narum; D. Hatch; A. J. Talbot; P. Moran; M. S. Powell (Journal of Fish Biology, 2008)
This study investigated diverse reproductive types in complex mating systems of steelhead Oncorhynchus mykiss . Postspawned steelhead (kelts) were sampled during attempted downstream migration over Lower Granite Dam on the Snake River, U.S.A. Multilocus microsatellite genotypes (14 loci) were used to assign unknown origin, kelt individuals to upstream populations of origin. Results indicated that iteroparity is a life‐history trait that remains in several tributaries of the Snake River basin despite strong selection against downstream adult passage because of hydroelectric dams. The largest populations of steelhead in the Snake River, however, were only weakly represented (Clearwater River = 7·5% and Salmon River = 9·4%, respectively) in the kelt steelhead mixture relative to the Grande Ronde River (18·2%), Imnaha River (17·4%), Pahsimeroi Hatchery (25·2%) and Asotin Creek (22·2%). A lack of correlation between population escapement size and kelt proportions ( P > 0·05) suggests that iteroparity was not uniformly expressed across populations, but was significantly negatively correlated with body size ( P

Incidence of squamous neoplasia of the cervix and vagina in women exposed prenatally to diethylstilbestrol (United States) - E. E. Hatch; A. L. Herbst; R. N. Hoover; K. L. Noller; E. Adam; R. H. Kaufman; J. R. Palmer; L. Titus-Ernstoff; M. Hyer; P. Hartge; S. J. Robboy (Cancer Causes & Control, 2001)

Nitrogen mineralization and microbial activity in permanent pastures amended with nitrogen fertilizer or dung - D. J. Hatch; R. D. Lovell; R. S. Antil; S. C. Jarvis; P. M. Owen (Biology and Fertility of Soils, 2000)